PENERAPAN METODE ROLE PLAYING DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MATERI KETENTUAN SALAT FARDU - Yusnidar (Journal of Community Devation, 2025)
This research aims to determine efforts to increase students' understanding of fardu prayers through the application of the Role Playing method to class II students at SD Negeri 14 Jaya. This research is descriptive in nature, namely by collecting data, compiling, analyzing data regarding efforts to improve learning outcomes regarding Islamic Religious Education about fardu prayers through the application of the Role Playing method to class II students at SD Negeri 14 Jaya. The research used was classroom action research (PTK) with two cycles. The implementation procedure refers to Arikunto where each cycle consists of four components, namely planning, implementation, observation and reflection. The research subjects were 30 class II students at SD Negeri 14 Jaya. The purpose of this research was to determine students' understanding of Islamic Religious Education lessons through the Role Playing method. As a result, students' understanding scores tend to increase if seen after implementing this method. This is proven to be cyclical I moment Role Playing. As a result, students' understanding scores tend to increase if seen after implementing this method. This was proven to be cyclical I during the pretest with a total of 1885, and an average score of 62.83. Meanwhile, during the posttest the number was 2150, and the average score was 71.66. Then cycle II during the pretest with a total of 2180, and an average score of 72.66. Meanwhile, during the posttest, the total number was 2,470, and the average score was 82.33. After implementing the Role Playing method, students understand the teacher's explanation better and feel happy.